Antifungal Activity of Streptomyces hygroscopicus JY-22 against Alternaria alternata and Its Potential Application as a Biopesticide to Control Tobacco Brown Spot - Lin Cai; Hongbao Zhang; Yongjie Deng; Weiqiang Tian; Guangjin Fan; Xianchao Sun (Agronomy, 2023)
Tobacco brown spot caused by Alternaria alternata is a devastating fungal disease endangering plant production. To effectively control brown spot disease, an antagonistic Actinomyces strain, Streptomyces hygroscopicus JY-22, was isolated from rhizospheric soil, which remarkably restrains the growth of phytopathogenic fungus Alternaria alternata. This antagonistic strain and its culture filtrate showed significant antifungal activity against Alternaria alternata. Firstly, the confrontation culture method of strains JY-22 and Alternaria alternata showed that Streptomyces hygroscopicus JY-22 had noticeable antifungal activity against Alternaria alternata, including inhibition of mycelial growth and mycelial morphological changes, compared with the control group. Furthermore, the culture filtrate of Streptomyces hygroscopicus JY-22 showed substantial inhibition of the mycelial growth and spore germination of Alternaria alternata in a dose-dependent manner. Additional studies revealed that these antifungal actions were mainly related to membrane-active mechanisms that increased membrane permeability and damaged the cell membrane, leading to changes in certain cytoplasmic properties, such as extracellular conductivity and ergosterol, MDA and soluble protein content. In detached-leaf and field experiments, foliar spraying with culture filtrate resulted in smaller lesions and a lower disease index than the control group. Taken together, these results suggest that Streptomyces hygroscopicus JY-22 and its culture filtrate have the potential to be a safe biopesticide for the bio-control of tobacco brown spot.